Analysis of Dynamic Damage Fractal and Energy Consumption Characteristics of Dolomite Marble - Ting Zuo; Zehu Zhao; Jianguo Wang; Xianglong Li; Zihao Tao; Changhui Yang (Shock and Vibration)
To investigate the damage fractal and energy dissipation of dolomite marble under blasting load, Dahongshan Copper Mine was selected as the test object and one-dimensional SHPB impact tests with different strain rates were carried out. The dynamic compressive strength, damage morphology, fractal fragmentation, and energy dissipation of the rock were analyzed. The results showed that the absorbed energy per unit volume and the crushing energy per unit mass of dolomite marble are closely related to the dynamic compressive strength. The fractal dimension D of dolomite marble increases with increasing strain rate, and the smaller the average block size of the rock, the degree of crushing deepens. In addition, as the incident energy increases, the crushing energy of the rock also increases, and the energy dissipation intensifies. Finally, after comparative analysis, the reasonable strain rate range is 68.14–77.61 s−1, and the reasonable specific energy absorption value range is 0.65–0.98 J/cm3. The fractal pattern of rock deformation and damage can be reasonably explained from the perspective of energy dissipation.